Prototype cooperative problem solving system for portfolio selection - Win, Aung Aung; Sadananda, Ramakoti; Gougeon, P.; Zhao, Ming (Bangkok : Asian Institute of Technology, 1991)
Cooperative Problem Solving is another promising technique of Artificial Intelligence. Many Cooperative Problem Solving Systems have been built for various complex application domain areas. Due to the nature of application domain in this study, and similarity of approach in problem solving, blackboard architecture is used to design and implement the prototype Cooperative Problem Solving System for Portfolio Selection. Theoretical considerations for developing this prototype system from the point of view of computer science as well as from the point of view of financial management are also discussed. The system has been developed for selecting partial portfolio for fixed rate coupon bonds. It contains two sub-systems. The first one which is called CPSS/SB, is for selecting bonds to be included in the portfolio. The second one which is used for forming portfolio with efficient fund distributions is named CPSS/FP. This proposed prototype is only the tip of the iceberg in this field of study. Possibilities of developing larger system of this kind are also discussed.
A Thesis submitted in partial fullfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Problem solving; Portfolio management